PEMILIHAN MODA TRANSPORTASI PELAJAR SEKOLAH DI KAWASAN K.H. AHMAD DAHLAN SAMARINDA - SANTOSO, EDI (KURVA S JURNAL MAHASISWA, 2017)
Activity studying in school will lead to a journey that can produce movements that ultimately require a choice of modes of transportation. The selection of modes to school students in the K.H. road area Ahmad Dahlan is not a random process, but is influenced by many factors. The problem is, what factors influence the learner in choosing the mode of transportation to the school and the mode of transportation that many students choose. The survey was conducted by spreading 342 questioners on students of SMPN 2, MTS. Normal Islam, SMKN 4, SMPN 37 on the road K.H. Ahmad Dahlan Samarinda. The survey results were analyzed by Analytical Hierarchy Process (AHP) to determine the mode selection factors. The analysis shows that the factors that affect school students in the area K.H. Ahmad Dahlan Samarinda in choosing the mode of transportation to school is a safety factor (33.654%), cost factor (23.316%), comfort factor (21.429%), time (19.601%). For many transportation modes in select school students in the area K.H. Ahmad Dahlan Samarinda is a mode of shuttle transportation (47,368%), private motor (41,520%), public transportation (7,310%), walking distance (3,216%), and for last private car (0,585%). From the results of the analysis obtained mathematical model of priority scale goals of school students in the area K.H. Ahmad Dahlan Samarinda namely Ymbp (0.0016), Ymrp (0.1069), Yau (0.0188), Yaj (0.1259), Ybk (0.0084).